2012
DOI: 10.1002/uog.11071
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis and outcome of fetal posterior fossa fluid collections

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
91
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 33 publications
3
91
0
1
Order By: Relevance
“…1,11,22 Therefore, the exact diagnosis and accurate prognosis given to the soon-to-be parents are crucial for the their understanding of the consequences of these malformations. The establishment of a diagnosis of PF malformation is based on several parameters, including anatomy, morphology, and biometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,11,22 Therefore, the exact diagnosis and accurate prognosis given to the soon-to-be parents are crucial for the their understanding of the consequences of these malformations. The establishment of a diagnosis of PF malformation is based on several parameters, including anatomy, morphology, and biometry.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some previously reported studies showed no benefit in diagnosing PF malformations by using MR imaging compared with ultrasound. 4,22,25 However, the increasing use of fetal MR imaging examinations after ultrasound screening to diagnose cerebral pa- thologies enables us to expand our biometric data to finer structures such as the vermian lobes and the brain stem. The vermian primary fissure is difficult to recognize by using ultrasound, making it difficult to differentiate between the vermian lobes.…”
Section: Discussionmentioning
confidence: 99%
“…As distinct defects associated with various pregnancy outcomes may have similar ultrasonographic appearance, prenatal differentiation remains an issue for the sonographers [24]. Despite challenging diagnosis, the current classification of the posterior fossa defects is even more confusing -the terminology and the knowledge about this group of CNS defects continue to evolve [25,26].…”
Section: Posterior Fossa Abnormalitiesmentioning
confidence: 99%
“…Despite challenging diagnosis, the current classification of the posterior fossa defects is even more confusing -the terminology and the knowledge about this group of CNS defects continue to evolve [25,26]. Nonetheless, some studies report up to 90% accuracy of neurosonography, when performed by experts [24].…”
Section: Posterior Fossa Abnormalitiesmentioning
confidence: 99%
See 1 more Smart Citation